Extraction and Characterization of Protease Enzyme from Moringa Leaves (Moringa oliefera Lamk.) - Fathimah, Azmy Nahdhiyati; Wardani, Agustin Krisna (Jurnal Teknologi Pertanian, 2014)
Proteases in moringa leaves have the potentials in industrial applications. This study was conducted to extract and characterize the proteolytic enzyme from moringa leaves (Moringa oliefera Lamk.). Protease was extracted from moringa leaves by homogenization with 100 mM potassium phosphate buffer pH 7.0 containing 10 ml 0.3% ascorbic acid and 10 ml 15 mM EDTA which were found to be the most effective extraction buffer and stabilizers. After centrifugation at 10.000 rpm,  protein  in  the  crude  extract  was  precipitated  using  60%  ammonium  sulfate following which the precipitate was redissolved in 50 mM potassium phosphate buffer pH 7.0 for dialyzed. The protease enzyme from Moringa leaves showed highest activity (2.45 U/mg) with the addition of 0.3% ascorbic acid and 15 mM EDTA. This result was selected for further precipitation with ammonium sulphate at 60% and then dialyzed against phosphate buffer. The level of purity of the enzyme increased to 3.21 fold. Protease enzyme A3E3 had optimal activity at pH 6 and temperature of 60 oC. The enzyme had good stability at temperatures 40-60 oC and pH 4–7. Enzyme showed highest specificity on casein substrate followed by whey, gelatin, BSA, egg albumin, and soy protein. This enzyme had a KM value 0,042 mg.mL-1 and Vmax 2.33 mg.mL-1.min-1. Enzyme activity increased with the addition of metal ions ZnCl2, FeCl2 and MgCl2. This enzyme is inhibited by the HgCl2 so can be categorized as a cysteine ​​protease. Protease band detected in the zymogram were estimated at 156.23 kDa.Keywords: characterization, extraction, moringa leaves, protease enzymes, stabilizers